Reading trajectories and semiosis in graphic design - Zantides, Evripides (My University, 2019)
Hierarchy of information in graphic communication is an essential parameter that contributes to readability, as well as in attracting the viewer’s gaze in a specific area of interest on the graphic surface. It organises the content in a specific order, and provides emphasis on visual points like crescendo or decrescendo would do in music. Both for print, or screen based applications, an entry point to a visual area defines where semiosis starts and the reading journey begins. While there are endless ways to enunciate this focal point, there are certain variables that are responsible for reading trajectories to be achieved. The aim of this paper is to consider these visual variables, which are size, shape, texture, value, colour, placement and orientation as suggested by Bertin (1967), and examine through specific examples like advertisements, logos and posters how they interrelate and create hierarchy for the construction of messages. In addition, the paper aspires to compare scientific data, collected using eye-tracking recordings of eye movements on advertisements with semiotic analysis. The findings show that design theory and semiotic analysis converge with scientific data, therefore it seems possible to predetermine and design trajectories for maximum readability in graphic and visual communication in general. Even though readability and legibility refer to the ease and clarity that a viewer navigates through the linguistic messages, the terms actually concern two separate notions. Readability refers to the comfort of the overall reading experience and how letterforms are arranged on a page or a website, whilst legibility is more specific, and concerns how well a typeface is designed with its letterforms distinguished among them. There are often graphic design examples with good legibility, but bad readability which in turn create attractive design trajectories or not. As such, the paper also seeks to discuss these parameters and the typographic factors that affect them for ultimate semiosis.
Keywords: Visual variables